Mother-infant conflict and "signalling" via breast milk - Mohd Shukri, Nurul Husna; Fewtrell, Mary; Wells, Jonathan (2023)
Lactation is a dynamic process in which the mother and the infant actively compete over how much of the mother's resources will be invested in breast milk during lactation. The infant's demand for milk can be expressed through behaviour, appetite, vocalisation, and/or non-nutritive suckling, while the mother's response can be shown in nursing behaviour, milk production, and/or milk composition. It is hypothesised that these relationships may shape infant behaviour and feeding, particularly appetite regulation, and may thus influence infant growth and development. However, there are many unanswered questions about this tug-of-war, including who is more in charge, how the mother allocates her energy economically to maximise her offspring's fitness, and whether, for instance, an abundance of maternal energy will result in a lessening of tension. However, it is also acknowledged that maternal emotion could influence breast milk synthesis and ejection, highlighting the need for minimising maternal stress or promoting relaxation during the postpartum period. Furthermore, the mother's energy reserves might be considerably depleted during the early postnatal period as she recovers from birth while continuing to invest in her infant, primarily through breast milk. Because breastfeeding requires high energy, postpartum distress may intensify the tug-of-war by affecting the mother's energy budget. Aiming to reduce this mother-infant conflict, we conducted a randomised controlled trial by manipulating the maternal psychological state using relaxation therapy (breastfeeding meditation) to see the effect on maternal stress, breast milk production, and infant behaviour and growth. The trial was conducted in Malaysia among first-time mothers and their full-term infants (n = 64), who were followed up on from birth to 16 weeks in three home visit sessions. Maternal stress and infant behaviour were assessed, infant growth was monitored, and breast milk samples were collected at all visit sessions. This trial found significant relaxation therapy intervention benefits for both mothers and infants, with the strongest evidence on maternal stress reduction and achieving optimal infant weight and BMI. The intervention therapy also showed a significant effect on infant behaviour, with longer infant sleeping duration, and on milk composition, with a greater decrease in milk cortisol concentrations at the early home visit. The pooled results from early to later home visits also revealed that the intervention might have long-term or cumulative consequences on elevating total energy levels in breast milk. Overall, listening to the relaxation treatment lowered maternal stress and modified the breast milk composition, which had an influence on infant sleeping behaviour and growth. The benefits of relaxation treatment on infant outcomes might be mediated by physiological signalling via changes in breast milk composition, or behavioural signalling via the influence on sleeping duration. In conclusion, encouraging relaxation during breastfeeding shifted the mother-infant tug-of-war toward a positive energy balance (reduced mother-infant conflict), leading to a greater energy investment in milk production and promoting healthy newborn growth. Nevertheless, it is important to consider the study's main limitations, which include the small sample size and non-blinded intervention due to the nature of behavioural intervention.